Getting started with Android app development - Gargenta, Marco; Safari eBooks ([S.l.] : Addison-Wesley, 2014)
"Getting Started with Android App Development LiveLessons is designed to give you a high level overview of Android as a development platform. It is a gentle introduction to what the Android operating system is, how we got here, what makes it fundamentally different than any other platform, and how to take advantage of its uniqueness. The course is designed for both technical managers seeking high-level understanding of the platform as well as developers warming up for a deep dive into programming for Android. By the end of this course, you will have a complete, high-level understanding of the entire operating system."--Resource description page.
Title from resource description page (viewed October 15, 2013).
Presenter, Marko Gargenta.
Keywords: Mobile computing -- Programming; Android (Electronic resource); Application software -- Development; Electronic books